2020
DOI: 10.3389/fmicb.2020.540404
|View full text |Cite
|
Sign up to set email alerts
|

The Total and Active Bacterial Community of the Chlorolichen Cetraria islandica and Its Response to Long-Term Warming in Sub-Arctic Tundra

Abstract: Lichens are traditionally defined as a symbiosis between a fungus and a green alga and or a cyanobacterium. This idea has been challenged by the discovery of bacterial communities inhabiting the lichen thalli. These bacteria are thought to contribute to the survival of lichens under extreme and changing environmental conditions. How these changing environmental conditions affect the lichen-associated bacterial community composition remains unclear. We describe the total (rDNA-based) and potentially metabolical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Interestingly, Frankiales that have previously been found in the Arctic can fix nitrogen and often live in symbiosis with actinorhizal plants ( Benson and Silvester, 1993 ; Nash et al, 2018 ). Klarenberg et al (2020) showed that members of the Acetobacterales dominate the bacterial community of the thalli of lichens that prevail on 8% of the world’s land surface, mainly in Arctic and Antarctic regions ( Beckett et al, 2013 ). Finally, both Propionibacteriales and Rhodobacterales were found in the active layer of thawing permafrost soil in the Arctic ( Inglese et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Frankiales that have previously been found in the Arctic can fix nitrogen and often live in symbiosis with actinorhizal plants ( Benson and Silvester, 1993 ; Nash et al, 2018 ). Klarenberg et al (2020) showed that members of the Acetobacterales dominate the bacterial community of the thalli of lichens that prevail on 8% of the world’s land surface, mainly in Arctic and Antarctic regions ( Beckett et al, 2013 ). Finally, both Propionibacteriales and Rhodobacterales were found in the active layer of thawing permafrost soil in the Arctic ( Inglese et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as also suggested by our results (Figures S3 and S4), comparative analyses of lichens from different environmental backgrounds have described the presence of an environment‐independent “core” microbiome that coexists together with distinct environment‐specific fractions of the total microbiome (Aschenbrenner et al, 2016; Grimm et al, 2021; Hawksworth & Grube, 2020). Further evidence suggesting a strong link between the adaptive potential of lichens and the variation in their microbiomes comes from studies that examined microbiome responses to long‐term climate warming scenarios (Klarenberg et al, 2020). Interestingly, the transition zones that we find to structure the individual components of lichen holobionts in our study coincide with major ecological zones (biomes) known to structure communities of macroorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…6 and Supplementary Table 5 ). Massilia and Granulicella are able to metabolize chitin for N and C sources 34 37 . Dyella and Sphingomonas as microbial resource can degrade a range of organic matters such as aromatic compounds 38 and phenol 39 .…”
Section: Discussionmentioning
confidence: 99%